إعادة هندسة العمليات كمدخل لتميز إدارة الموارد البشرية - أحلام, خان (Recherches économiques et managériales; Vol. 12 (2012): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (DÉCEMBRE))
في ظل البيئة المتغيرة والتطورات المتسارعة التي تشهدها منظمات الأعمال، ونتيجة الإعتماد المكثف على تكنولوجيا المعلومات، أصبح لزاما على المؤسسات البحث عن أساليب إدارية جديدة تتلاءم والبيئة الحالية والتخلص نهائيا من الأساليب التقليدية، وهو ما يوفره تبني أسلوب إعادة هندسة العمليات. هذا الأخير يشكل ثورة في عالم الأعمال ودعوة صريحة لإعادة النظر في كل ما تقوم المنظمة من عمليات وإجراءات ومهام....      لتحقيق تحسينات ملموسة وتغييرات جذرية في مختلف المجالات عموما وفي إدارة الموارد البشرية بشكل خاص، مما يساهم في تطويرها وتميزها وتحقيقها للقيمة المنتظرة منها.     وفي هذه الورقة البحثية سنحاول تسليط الضوء على طبيعة العلاقة بين أسلوب إعادة الهندسة وإدارة الموارد البشرية، وكيف بات من الضروري للمؤسسات إعادة هندسة مواردها البشرية لتحقيق التميز الإداري.     الكلمات المفتاحية: إعادة هندسة العمليات، تكنولوجيا المعلومات، إدارة الموارد البشرية، إعادة هندسة الموارد البشرية.           In light of the changing environment and the rapid developments taking place in the business organizations, and as a result of intensive reliance on information technology, it has become imperative for organizations to research for new management methods adapted to the current environment and the final elimination of the traditional methods, which is provided by the adoption re-engineering processes method. This latter represents a revolution in the world of business and an explicit invitation to revisit all the Organization, processes and procedures and functions to achieve tangible improvements and radical changes in the various fields in general, and in human resources management in particular, thus contributing in the development, excellence and achievement of the value expected.    In this paper we will try to focus on the nature of the relationship between the re-engineering method and human resources management, and how it is necessary for organizations to re-engineer human resource to achieve excellence. Key words: Business Process Reengineering, information technology, Human resources management, reengineering Human resources.